Proses Pembelajaran Teater Tradisional Lenong Pada Kelas X di SMA Negeri 11 Palembang - Yuningsih, Dwi; Hasan, Hasan; Ilhaq, Muhsin (ANTHOR: Education and Learning Journal, 2022)
The problem in this research is how the process of learning traditional long theater in class X at SMA Negeri 11 Palembang, the research leads to a type of descriptive qualitative research. This study aims to find out and describe how the learning process for traditional lenong theater in class X at SMA Negeri 11 Palembang with the script "Jakarta Children Speak Palestine". Data collection techniques in this study were observation techniques, interviews, and documentation. The results obtained in research on traditional lenong theater were quite good, because the teacher made preparations, carried out evaluations, and used well-organized methods. The role-playing method is a method to support learningeffectiveness which is seen in the average value of 94.41 as a result of the value obtained by students.